Is accessibility inequality morally relevant?: An exploration using local residents' assessments in Modesto, California. (February 2022) - Cooper, Erin; Vanoutrive, Thomas
Abstract: Research on transportation and accessibility disadvantage provides normative frameworks to assess and remedy accessibility disadvantages. In this paper, we focus on the concept of sufficient accessibility by exploring the ethical concept of sufficientarianism, and addressing questions such as what people value and when people have "enough" of a particular good. We include local perspectives from an understudied location, Modesto, California, through semi-structured interviews which address individual accessibility situations, challenges, and coping strategies. The interview results align with sufficientarianist ideas, which focus on people having access to basic needs and to what they value. Some respondents did not want major increases in their accessibility, only moderate or reasonable improvements. Respondents showed that they valued autonomy in accessibility decisions through choosing accessible housing locations and recognizing trade-offs among various options. The participants lived locally, and did not envy the long commutes of some of the higher income residents. These responses suggest positionality was not a main consideration for their mobility decisions. This reminds us that there is a limit to what accessibility can achieve, and general, societal improvements to accessibility may not provide needed resources. Additionally, the disparate lifestyles of residents can lead us to question the value of creating sufficiency thresholds, something often discussed in accessibility research. We conclude that from a sufficientarianist perspective, what matters most is not inequality in accessibility, but supporting local, convenient lifestyles, taking into account what people value. While, unethical inequalities do exist, inequalities in accessibility may not be morally relevant in all circumstances. This suggests we try to understand the cause behind observed inequalities, especially with regard to political decision making, to create a community of political equals who together shape their accessibility environment. Highlights: Transportation studies tend to restrict Sufficientarianism to a threshold concept. Accessibility thresholds are relevant for basic need assessments. General access improvements will not benefit all less-advantaged groups. Better access is not always a positional good that indicates a better quality of life. Often a lack of accessibility reflects a lack of democratic decision-making.